Determinants of quality and productivity in automobile services: MADM approaches and empirical analysis - Gençer, Yasin Galip. (Thesis (Ph.D.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2016., 2016)
Quality and productivity are two important concepts for all businesses including automobile services. This research study is a PhD dissertation at Bogazi9i University and has the goal of examining the determinants of quality and productivity in automobile services by Multi Attribute Decision Making and empirical analysis. Thus it includes three separate parts all of which are associated with the automobile sector. The first part of the study aims to measure productivity in automobile aftersales business whereas the second part looks for a scale to measure the service quality in automobile aftersales, and the last part uses this AutoServQual scale to compare automobile brands in Turkey. A literature review of related theories done in all parts includes Multi Attribute Decision Making Theory in the first part, Service Quality Measurement Methods in the second part, and the Turkish Automotive Industry in the last part. Data Envelopment Analysis is selected to compare automobile aftersales services at stations of a specified brand in Turkey. In the second part, ServQual scale is selected for adaption to the automobile services by the name of AutoServQual using studies of focus groups, item generation and pilot survey; this new scale is now available for use in international studies in the area of automobile services. The last part of the study compares different automobile brands by using the results of a recently generated AutoServQual scale to find out the strong and weak sides of automobile aftersales services in Turkey with the use of SPSS and AMOS software. iv
Keywords: Automobile industry and trade -- Turkey -- Quality control.; Automobile industry and trade -- Customer servicese -- Turkey.